Characterization of wet granular avalanches in controlled relative humidity conditions - Gomez Arriarán, I. (2015)
This work focuses on the influence of the relative humidity (essentially due to atmospheric conditions) on themany granular media behaviours. To this end, the experimental evolution of the avalanche characteristic anglesof continually tilted granular packing was studied for a wide range of relative humidities in very well controlledconditions (between 5 and 90%). The stability angles were measured for fully developed avalanches. The relationshipbetween the relative humidity (ϕ) and cohesion of granular media (directly related to cohesion forcesbetween grains) was then established to identify the different cohesive states of a wet granular medium usinga reliable and reproducible testing methodology. Finally, a relationship between the hygroscopic equilibriumtime and the stability of the granular packing is discussed.